Harnessing Collaborative Partnerships Toward Sustainability: A Community-Based Learning Initiative - Patrick C. Exmeyer; Henry Cunningham; Eli T. Miller; Caleb Martin; Morgan Bentley; Ellie Nelson (Journal of Community Engagement and Scholarship)
Sustainable planning is a vital tool for municipalities seeking to promote equitable economic and environmental development within their communities. Successful implementation of sustainability initiatives involves many factors, ranging from engaging stakeholders for input to combining and leveraging existing resources from both community and institutional stakeholder groups. This study illustrates how collaborative partnerships formed through community-university relationships can facilitate community-based learning and community-engaged scholarship initiatives centered on sustainable planning. Using the example of a student-led tree audit in a partner community, the study demonstrates how community-based learning and community-engaged scholarship principles may be applied to achieve municipal sustainability goals. The study outlines how community-based learning agendas formed through community-institution collaborative partnerships can generate actionable insights for communities pursuing sustainability initiatives.